Effectiveness of nutrition education on stunting prevention behavior in mothers under five - Risna Ayu Rahmadani; Ari Setiawati; Indrawati Aris; Anita Lontaan; Prasetyowati Prasetyowati (Edukasi Ilmiah Indonesia, 2025)
Introduction: Stunting is a global health problem that impacts children's growth and development. One of the main factors contributing to stunting is the lack of maternal knowledge about balanced nutrition. Nutrition education is expected to increase mothers' understanding of healthy eating and toddler stunting prevention practices. This study aims to analyze the effectiveness of nutrition education on changes in maternal behavior in preventing stunting in toddlers. Materials and Methods: This study uses a quasi-experimental design with a pretest-posttest approach with a control group. The sample consisted of mothers with toddlers, selected by purposive sampling. The intervention group was given nutrition education through counseling media and interactive discussions, while the control group did not receive the intervention. Results: The study showed a significant increase in mothers' knowledge and practice of nutrition after being given nutrition education (p<0.05). In addition, there were substantial differences between the intervention and control groups regarding stunting prevention behavior. Conclusions: Nutrition education has been proven effective in increasing maternal knowledge and behavior and preventing toddler stunting. Therefore, public health programs need to expand nutrition education interventions to reduce stunting incidence.